Петрология и формационная принадлежность габбро-долеритов Рудня-Базарской интрузии (Волынский мегаблок Украинского щита) - Митрохин, А.В.; Омельченко, А.Н.; Андреев, А.А. (Мінералогічний журнал, 2010)
Рудня-Базарская базитовая интрузия пространственно ассоциирует со сложным Коростенским плутоном анортозит-рапакивигранитной формации в пределах Волынского мегаблока Украинского щита. Изучены минералогопетрографические особенности и формационная принадлежность габбро-долеритов Рудня-Базарской интрузии. Выполнено сравнение со субщелочными базитовыми дайками восточной части Волынского мегаблока и габброидами коростенского комплекса. Доказана родственность габбро-долеритов Рудня-Базарской интрузии базитам коростенского комплекса. Определена их фосфор-титановая минерагеническая специализация. Рудня-Базарська базитова інтрузія просторово асоціює зі складним Коростенським плутоном анортозит-рапаківігранітної формації в межах Волинського мегаблоку Українського щита. Вивчені мінералогопетрографічні особливості та формаційна приналежність габро-долеритів Рудня-Базарської інтрузії. Виконано порівняння з сублужними базитовими дайками східної частини Волинського мегаблоку та з габроїдами коростенського комплексу. Доведена спорідненість габро-долеритів Рудня-Базарської інтрузії з базитами коростенського комплексу. Визначена їх фосфор-титанова мінерагенічна спеціалізація. The Rudnya-Bazarska mafic intrusion (RBI) spatially associates with the Korosten gabbro-anorthositemangerite- rapakivi-granite complex within Volyn block of the Ukrainian Shield. The RBI crosscuts the metamorphic rocks of the Nedashky block that represents an ancient folded basement of the Korosten pluton. The Nedashky block is located in the least exposed northeast part of the Korosten pluton that, therewith, got in a zone of resettlement after the Chernobyl disaster. Thus, this area is one of the least investigated within the crystalline basement of the Ukrainian Shield. The recent regional geological researches in this region have been executed in the 70's of the 20th century when carrying out geological survey 1 : 50000 scale. Some results of these researches have been generalized in reports about the geological survey, but, unfortunately, are not they published in the scientific literature. The authors have summarized all data about geological position of the RBI and have studied available drill-cores from sparse boreholes drilled in the area of the Nedashky block. RBI occurs as linearly extended body with north-east strike controlled by the Teterev fracture zone. It is traced at a distance more than 18 km with thickness of 1—1.5 km. In the significant area the RBI is covered by mesozoic to cainozoic sediments up to 70 m. On the north-east flank it is covered by quartz porphyries of the Vilcha suite with U-Pb zircon isotope age of 1770 Ma. RBI breaks through the migmatites of the paleoproterozoic Zhitomir complex (2010 Ma), a possible substratum for which was gneisses of amphibolitic facies and shales of the Teterev group. Several veins of aplitic-pegmatitic granites, crosscutting the RBI rocks, were attributed to Korosten complex. The authors investigate mineralogical and petrographic features of the mafic rocks of the Rudnya-Bazarska intrusion. A comparison is made with the subalkaline mafic dikes widely distributed in the eastern part of the Volyn block and with the Korosten complex gabbroic rocks. RBI is formed by hypabyssal gabbroic rocks with subalkaline features. The majority of the investigated samples are unaltered rocks with well expressed medium-grained subophitic and gabbro-ophitic textures, which make them similar to the gabbro-dolerites of Zvizdal- Zalesye, Skuraty, Belokorovichy and some others subalkaline basic dykes, widespread in eastern part of the Volyn block at the vicinity of the Korosten pluton. The similarity is supported by the olivine-bearing composition of the RBI basites with apatite-ilmenite paragenesis of accessory minerals. At the same time, a careful comparison of RBI basites with the gabbrodolerites of the neighboring Zvizdal-Zalesye dyke shows some essential distinctions in composition and microtextural features of the investigated rocks. The main characteristic feature of RBI rock compositions is their greater modal diversity especially in respect of quantitative contents of plagioclase and mafic, two-pyroxen paragenesis with usual prevalence of orthopyroxene (inverted pigeonite) above augite, more evolved mafic minerals, greater variations in concentration of Fe-Ti oxide-ore minerals and apatite. The textural features of RBI rocks are a wide spread of marginal coronary textures around olivine and pyroxenes as well as subsolidus dissolution microstructures in pyroxenes, ilmenite and Ti-magnetite. A lot of mineralogical and petrographical features of RBI rocks correspond to the Korosten complex gabbroids, especially to their variations with gabbro-ophitic textures which are frequent among basites of this complex. This together with geochemical features allows to expect the phosphorus-titanium ore specialization for the RBI. Physical and chemical conditions of RBI mineral paragenesis formation demands additional researches.